SISTEM INFORMASI PENERAPAN E-CRM UNTUK MENINGKATKAN KUALITAS LAYANAN PELANGGAN DI FAMILY BOX PEKANBARU - Sri Astuti Handayani; Elvira Asril (LPPM STMIK Royal Kisaran, 2023)
Abstract: Family Box is a karaoke entertainment venue located on Jl. HR Soebrantas Panam Pekanbaru, during this pandemic the family box has experienced a decrease in customers so that the family box needs to remanage services at the Family box. Family Box is an entertainment place that has a lot of competition with other karaoke places such as Koro-Koro, Happy Puppy and so on. During this pandemic, the family box overcame the competition by providing free 1 hour karaoke for customers who order 1 hour karaoke with the condition that they follow and post the customer's personal Instagram or by ordering food that has been set by the family box. And the family box also provides free Voucher Room for customers who order food at karaoke with the condition that they order food which is also specified by the family box. With this problem the researcher wants to build a family box management information system in an effort to improve management in the family box. For this reason, the company implements Electronic Customer Relationship Management (E-CRM) to best serve customers so that customers feel satisfied and valued by the company. With CRM, companies will get detailed information about customers. The information is in the form of customer personal data, criticisms, suggestions and whatever is needed by the customer, so that the company can provide responses, services and changes according to what the customer wants. Keywords : information system; CRM; service; customer Abstrak :Family Box adalah tempat hiburan karaoke yang terletak di Jl.HR Soebrantas Panam Pekanbaru, dimasa pendemi ini family box mengalami penurunan pelanggan sehingga Family Box perlu melakukan pengelolaan ulang terhadap pelayanan di Family Box. Family Box tempat hiburan yang banyak memiliki persaingan dengan tempat karaoke lainnya seperti Koro-Koro, Happy Puppy dan lain sebagainya. Pada masa pendemi ini family box mengatasi persaingannya dengan cara memberi free karaoke 1 jam bagi customer yang memesan 1 jam karaoke dengan syarat mengikuti dan memposting instagram pribadi customer atau dengan memesan makanan yang sudah ditetapkan Family Box. Dan Family Box juga memberikan Free Voucher Room bagi customer yang memesan makanan pada saat karaoke dengan syarat memesan makanan yang juga ditetapkan Family Box. Dengan permasalahan ini peneliti ingin merancang dan membangun sebuah sistem informasi pengelolaan Family Box dalam upaya peningkatan pengelolaan di Family Box. Untuk itu, perusahaan menerapkan Electronic Customer Relationship Management (E-CRM) untuk melayani pelanggan dengan sebaik- baiknya agar pelanggan merasa puas dan dihargai oleh perusahaan. Dengan CRM, perusahaan akan mendapatkan informasi yang rinci mengenai pelanggan. Informasi itu berupa data pribadi pelanggan, kritik, saran dan apa saja yang dibutuhkan oleh pelanggan, sehingga perusahaan dapat memberikan tanggapan, pelayanan, serta perubahan-perubahan yang sesuai dengan apa yang diinginkan pelanggan. Kata kunci : sistem informasi; CRM; pelayanan; customer